Anti-proliferative and apoptosis-inducing effect of theabrownin against non-small cell lung adenocarcinoma A549 cells - Feifei Wu; Li Zhou; Wangdong Jin; Weiji Yang; Ying Wang; Bo Yan; Wenlin Du; Qiang Zhang; Lei Zhang; Yonghua Guo; Jin Zhang; Letian Shan; et al. (Frontiers Media S.A., 2016)
With the highest cancer incidence rate, lung cancer, especially non-small cell lung cancer (NSCLC), is the leading cause of cancer death in the world. Tea (leaves of Camellia sinensis) has been widely used as a traditional beverage beneficial to human health, including anti-NSCLC activity. Theabrownin (TB) is one major kind of tea pigment responsible for the beneficial effects of tea liquor. However, its effect on NSCLC is unknown. The aim of the present study was to evaluate anti-proliferative and apoptosis-inducing effect of TB on NSCLC (A549) cells, using MTT assay, morphological observation (DAPI staining), in situ terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay, and annexin V/PI flow cytometry. Subsequently, the expression of several genes associated with cell proliferation and apoptosis were detected by real time PCR assay to explore its potential underlying mechanism. TB was revealed to inhibit cell proliferation of A549 cells in a concentration-dependent and time-dependent manner. Morphological observation, TUNEL assay and flow cytometric analysis evidenced an apoptosis-inducing effect of TB on A549 cells in a concentration-dependent manner. The real time PCR assay demonstrated that TB down-regulated the expression of TOPO I, TOPO II, and BCL-2, and up-regulated the expression of E2F1, P53, GADD45, BAX, BIM, and CASP 3,7,8,9, which suggests an activation of P53-mediated apoptotic (caspase-dependent) pathway in response to TB treatment. The western blot analysis showed a similar trend for the corresponding protein expression (P53, Bax, Bcl-2, caspase 3,9, and PARP) and further revealed DNA damage as a trigger of the apoptosis (phosphorylation of histone H2A.X). Accordingly, TB can be speculated as a DNA damage inducer and topoisomerase (Topo I and Topo II) inhibitor that can up-regulate P53 expression and subsequently modulate the expression of the downstream genes to induce cell proliferation inhibition and apoptosis of A549 cells. Our results indicate that TB exhibits its anti-NSCLC activity via a P53-dependent mechanism, which may be a promising candidate of natural product for anti-cancer drug development in the treatment of NSCLC.